Balancing the human and spiritual worlds: Ritual, music, and dance among Dusunic societies in Sabah - Jacqueline Pugh-Kitingan (Cambridge University Press, 2014)
The term mitimbang (“balanced”) is commonly used in indigenous Dusunic languages in Sabah, the east Malaysian state on northern Borneo, to describe an ideal relationship between two parties. In traditional worldviews, the ideal universe is balanced between the physical and spiritual worlds. This balance can be disrupted by sinful human actions that anger the spiritual world and affect the physical world. Appropriate rituals must be performed to restore the balance or neutrality between the human and spiritual worlds. Chanting of long sacred ritual poetry or rinait by priestesses, gong ensemble music, and dance are essential elements in major traditional ritual events. Gong ensemble music in ritual is generally believed to be a conduit through which the human and spiritual worlds merge. Dancing by priestesses in ritual events acts out transactions taking place between the human and spiritual worlds. This article compares and contrasts the roles of music and dance in two examples of ritual ceremonies from two different Dusunic societies. The first is the Moginum, a family-level ceremony from the Rungus of northern Sabah, while the second is the community-wide Mamahui Pogun of the Lotud of Tuaran District on the west coast. The article also explains why Rungus gong ensemble music can be performed at non-ritual celebrations, whereas the performance of Lotud ritual gong ensemble music is confined to its ritual context.